2011
DOI: 10.1016/j.jneuroim.2010.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in CNS autoimmunity induced by mimicry epitope for PLP 139–151 in SJL mice

Abstract: Development of multiple sclerosis (MS) is more prevalent in females than in males, but the underlying mechanisms are not clear. Microbial infections have been suspected as triggers of MS and it is not known whether gender differences in reactivity to environmental antigens contribute to the disease pathogenesis. We demonstrated that ACA 83-95, a mimicry epitope from Acanthamoeba castellanii for proteolipid protein (PLP) 139-151, induces clinical signs of encephalomyelitis in both male and female SJL mice. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…On the contrary, the pathogenic potential of effector T cells is directly tested in AT-EAE protocol by transferring antigen-stimulated lymph node or spleen cells generated from previously immunized mice, thus eliminating the need to immunize naive recipients prior to disease induction. Figure 3a shows that SJL mice immunized with ACA 83-95 developed clinical signs of EAE reminiscent of disease induced by the cognate peptide PLP 139-151 (Tuohy, et al, 1989, Massilamany, et al, 2010, Massilamany, et al, 2011. Verification of these results in AT-EAE protocol clearly indicated that the disease-induction by ACA 83-95 requires the mediation of antigen-sensitized T cells (Fig.…”
Section: Autoimmunity In the Mediation Of Amoebic Encephalitismentioning
confidence: 87%
See 4 more Smart Citations
“…On the contrary, the pathogenic potential of effector T cells is directly tested in AT-EAE protocol by transferring antigen-stimulated lymph node or spleen cells generated from previously immunized mice, thus eliminating the need to immunize naive recipients prior to disease induction. Figure 3a shows that SJL mice immunized with ACA 83-95 developed clinical signs of EAE reminiscent of disease induced by the cognate peptide PLP 139-151 (Tuohy, et al, 1989, Massilamany, et al, 2010, Massilamany, et al, 2011. Verification of these results in AT-EAE protocol clearly indicated that the disease-induction by ACA 83-95 requires the mediation of antigen-sensitized T cells (Fig.…”
Section: Autoimmunity In the Mediation Of Amoebic Encephalitismentioning
confidence: 87%
“…2; Massilamany, et al, 2010, Massilamany, et al, 2011. The epitope termed, ACA 83-95 is derived from rhodaneserelated sulfur transferase of Acanthamoeba.…”
Section: Autoimmunity In the Mediation Of Amoebic Encephalitismentioning
confidence: 99%
See 3 more Smart Citations